Role of the Pre-neck Appendage Protein (Dpo7) from Phage vB_SepiS-phiIPLA7 as an Anti-biofilm Agent in Staphylococcal Species - Gutiérrez, Diana; Briers, Yves; Rodríguez-Rubio, Lorena; Martínez, Beatriz; Rodríguez, Ana; Lavigne, Rob; García, Pilar (Frontiers in Microbiology, 2015)
Staphylococcus epidermidis and Staphylococcus aureus are important causative agents of hospital-acquired infections and bacteremia, likely due to their ability to form biofilms. The production of a dense exopolysaccharide (EPS) matrix enclosing the cells slows the penetration of antibiotic down, resulting in therapy failure. The exopolysaccharide depolymerase (Dpo7) derived from bacteriophage vB_SepiS-phiIPLA7, was overexpressed in E. coli and characterized. A dose dependent but time independent response was observed after treatment of staphylococcal 24 h-biofilms with Dpo7. Maximum removal (>90%) of biofilm-attached cells was obtained with 0.15 µM of Dpo7 in all polysaccharide producer strains but Dpo7 failed to eliminate polysaccharide-independent biofilm formed by S. aureus V329. Moreover, the pre-treatment of polystyrene surfaces with Dpo7 reduced the biofilm biomass by 53-85% in the 67% of the tested strains. This study supports the use of phage-encoded exopolysaccharide depolymerases to prevent and disperse staphylococcal biofilms, thereby making bacteria more susceptible to the action of antimicrobials.